THEY COME IN DIFFERENT SHAPES: A CRITICAL ANALYSIS OF TEACHER TYPES - CHITIGA, MIRIAM (IJRDO- Journal of Educational Research, 2017)
This essay is an enquiry into the different dispositions and make-up of teachers. This characterization and grouping of teachers is of essence because it will enable teacher educators to reflect on the kind of teachers they produce each year .This reflection will enable providers of teacher educators to rethink about the approaches they have always been employing in teaching teachers with a view to establishing new trajectories of teacher education to meet the educational needs of the millennium. Corollary to the mentioned goal is the need to focus on the different dispositions of teachers with a view to adopt new teaching methods to the end of improving the integrity, efficiency and professionalism of the teaching profession.